2017
DOI: 10.4269/ajtmh.16-0411
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance at Private Laboratories Identifies Small Outbreaks of Hepatitis E in Urban Bangladesh

Abstract: Abstract. Although large outbreaks of hepatitis E are regularly identified in south Asia, the majority of south Asian countries lack surveillance systems for this disease, which has hindered burden of disease estimates and prioritization of resources for prevention. Our study aimed to identify small hepatitis E outbreaks through a sentinel private laboratory in Dhaka, Bangladesh. We identified patients with detectable IgM antibody against hepatitis E virus. We defined a small outbreak as at least two laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…A previous study conducted in a private laboratory in Dhaka identified small outbreaks of HEV infections throughout the year [9]. The patients in our surveillance hospitals might be sporadic cases of hepatitis E or cases from small outbreaks that occurred throughout the year, as was observed in that study [9]. There are a number of limitations of our study.…”
Section: Characteristicsmentioning
confidence: 77%
See 1 more Smart Citation
“…A previous study conducted in a private laboratory in Dhaka identified small outbreaks of HEV infections throughout the year [9]. The patients in our surveillance hospitals might be sporadic cases of hepatitis E or cases from small outbreaks that occurred throughout the year, as was observed in that study [9]. There are a number of limitations of our study.…”
Section: Characteristicsmentioning
confidence: 77%
“…HEV can cause sporadic cases and small outbreaks [9], but is often responsible for epidemics in Asia and many parts of Africa [1,[10][11][12]. The most common clinical feature of symptomatic HEV infection is jaundice; it is symptomatically indistinguishable from other causes of acute viral hepatitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no outbreak reported during the study period, the possibility of unidentified and/or unreported outbreak cannot be excluded. Smaller outbreaks often remain unreported due to lack of active surveillance in Bangladesh [30]; therefore, it is possible that viral strains characterized in this study may include outbreak strains.…”
Section: Discussionmentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Med 2019;9:a031732 use of untreated water from rivers or shallow wells for drinking, failure of water treatment plants, and inadequate chlorination of the water supply (Hakim et al 2017). A large commercial laboratory in Dhaka, Bangladesh has found HEV infection to be the most frequent etiology of clinical hepatitis throughout the year (Sazzad et al 2017). Surveillance of patients with acute jaundice in Northern Uganda has found most cases to be from HEV infection throughout the year (Gerbi et al 2015).…”
Section: Epidemiology Of Genotype 1 and 2 Hev Infectionsmentioning
confidence: 99%